Identification of key career indicators in portuguese football players - Monteiro, Ricardo (2021)
The aim of this study was to describe and identify the weight of some key career indicators (KCI) on the competitive level of retirement (professional vs. non-professional) of Portuguese football players. Three thousand five hundred retired Portuguese football players born between 1950 and 1989, and registered on Portuguese Football Federation were considered in this study. Descriptive analysis and a multivariable binary logistic regression model were performed to assess the relationship between the mastery stage development variables and the competitive level of retirement of football players. The results highlighted that the KCI first senior registration level, number of seasons in mastery stage, number of total games as senior player, number of total games in retirement season, and the age of the last best result achieved contribute to explain and predict the competitive level of retirement of Portuguese football players. The tendencies identified and their impact on the competitive level of retirement could be important implications on awareness and definition of management and support programs of players’ careers.